Investigate the Water Activity of Different Solutions According to Solute Concentration for Preparing Wet Filtration Solution - Minh Chau, Nguyen; Thanh Dong, Pham; Minh Viet, Nguyen; Dinh Khai, Do; Thi Thuy, Nguyen; Thi Phong Huong, Trinh; Duc Khanh, Tran; Ha Giang, Vu; Van Ha, Hoang (VNU Journal of Science: Earth and Environmental Sciences, 2022)
According to the World Health Organization (WHO), air pollution ranks 6 th among the leading causes of death globally. The wet porous membrane filter has been widely used in dust removal, VOCs, and acid gas absorption. The wet filtration solutions need to ensure a low water activity that limits the release of moisture into the air, inhibits microbial growth, and can absorb dangerous gases. This study investigated the water activity of NaCl, NaNO 3 , K 2 CO 3 , KCl, K 2 SO 4 , Mg(NO 3 ) 2 , MgCl 2 , and CaCl 2 solutions at different concentrations to saturation at 25 °C. NaCl and NaOH solutions are not only investigated at different concentrations but also investigated the effect of temperature in the range of 0-40 °C. Some solution formulas are suggested that ensures the following properties: low water activity, antifungal, antibacterial and acid gas absorption.